PENGARUH MANAJEMEN LABA DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITIES SERTA IMPLIKASINYA TERHADAP FIRM VALUE PADA PERUSAHAAN KELOMPOK LQ 45 DI BURSA EFEK INDONESIA - Endang Hadiyanti; Kamaliah Kamaliah; Desmiyawati Desmiyawati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
This study was conducted to test empirically 1) The effect of earningsmanagement on the disclosure of CSR, 2) Influence of the audit committee ondisclosure of CSR, 3) Effect of mediation CSR disclosure of the relationshipbetween earnings management and firm value, 4) Effect of mediation CSRdisclosure of the relationship between the audit committee and the firm value, and5) The effect of CSR disclosure on firm value. The object under study is LQ 45group company listed in Indonesia Stock Exchange period 2013 to 2014.Testing is done with path analysis by using SPSS version 21. Prior to testing,conducted prior test data normality and linearity test. The results showed that 1)Earnings management influence on CSR 2) The audit committee has an effect onthe disclosure of CSR 3) Disclosure CSR mediates the effect of earningsmanagement on firm value 4) Disclosure CSR mediates the influence of the auditcommittee of the firm value 5) Disclosure CSR affect the firm value.